Desempenho de matrizes de corte suplementadas com minerais orgânicos e inorgânicos - Pedro, Douglas (2012)
This study was conducted to investigate the effect of organic and inorganic minerals, in broiler breeders Cobb®500. It was used 4 treatments: PI= 100% mineral inorganic premix; PO= 100% mineral organic premix; PI+PO= 70% mineral inorganic premix + 30% mineral organic premix and PI+Zn= 100% mineral inorganic premix, except zinc mineral, that was 70% inorganic form and 30% organic form. The trace minerals were: zinc, manganese, selenium, copper and iron, Iodine is added to the inorganic salt in its state. Corn and soybean meal diets were used. 440 hens and 40 roosters with 51 weeks of age were used. The experiment was conducted between 51st and 65th weeks of age of birds. The production parameters and quality parameters analyzed were: laying rate, hatching rate, egg weight, specific gravity, embryonic mortality and quality progeny. The parameters of progeny analyzed were: body weight gain, feed intake, feed conversion and mortality. The birds were housed in an experimental house at Poultry Laboratory (LAVIC) of the Federal University of Santa Maria with 20 floor pens of 4.61m2. The design was completely randomized with four treatments and five pen replicates with 22 hens and two roosters each. To evaluate the progenies two evaluations were performed of 1 the 21 days. Each evaluation used 320 male chicks one day of age, from eggs produced with the arrays of 55 and 60 weeks of age. For each evaluation, was adopted the same design used in the evaluation of the broiler breeders, resulting in four treatments groups with 10 replicates of 8 males birds each. Under the conditions and time that the experiment was conducted, the use of organic minerals had no significant effect (P>0.05) on the parameters evaluated in the broiler breeders and progeny, during the study period. Keywords: Zootechnical indexes. Minerals. Broiler breeders